Leakage current paths in transformer-less single-phase inverter topology with PWM mitigation - Khan, Md. Noman Habib (Kulliyyah of Engineering, International Islamic Unniversity Malaysia, 2014)
This dissertation studies single-phase transformer-less inverter topology for exploring the issue of common mode (CMV) voltage development, suggesting technique for reducing the resulting leakage current. The technique of AC and DC decoupling is explained; suggesting how such approaches address the CMV problem, although reducing the leakage current considerably but generating the problem in the form of more harmonic generation and at the cost of smaller voltage output. The suggested technique in this work is basically a modified topology by adding on an additional switch along with a diode. The diode is added for dealing the issue of CMV further effectively. A bridge-based transformer-less inverter topology is proposed, producing simulations results with preferential advantage. The technique is further verified by adding a series resistance to show how the leakage current is reduced for different resistive values. Moreover, output voltage is shown for some transformer-less topologies with reduced leakage current and that is verified and compared with the topology for common leakage path in this proposed topology. On the other hand, different paths are shown and as well as leakage current for those paths is also shown for both 50% and 75% duty ratio conditions with values.